High-speed video analysis of crown formation dynamics of controlled weapon-head impacts on to three surface types. Issue 2 (3rd April 2017) - Stotesbury, Theresa; Illes, Mike; Vreugdenhil, Andrew
ABSTRACT: This work explores the crown formation dynamics of blunt force impact onto a thin film of sheep's blood. Three weapons – a hammer head, a simulant baseball bat, and a metal bar – were used to impact blood on fibreboard, cloth, and sponge. Impact velocity was controlled using a custom impact device. High-speed videos were collected and analyzed with motion tracking and computing software. Interestingly, crowns were not observed to form in seven out of nine trials where each weapon struck the bloodied sponge. The widths and heights where observable crowns formed were measured and ranged between 0 to 105 mm and –0.4 to 36 mm, respectively. Bloodied material type was observed to influence the size and shape of the crown; however, the weapon heads used in this study did not. Three unusual cases of rim instability were observed where droplets were sent in the opposite direction of the expanding crown. This work supports the idea that the formation dynamics of mechanisms caused by blunt force impact are complex. Observable crowns can form with a range of geometries and subsequently produce droplets that originate at points different from the contact interface between the weapon head and blood.